Nasoalveolar molding in early management for newborn with labiognatopalatoschizis - Raodah; Sutiyo; Irfan Dammar (Indonesia Prosthodontic Association, 2023)
A 1-week-old female infant with bilateral cleft lip and palate (CLP) was referred to the Department of Prosthodontic, Hasanuddin University Dental Hospital. The nutrition was managed through a nasogastric tube. The patient was in primary need of appliance that could support the feeding. Intraoral examination revealed bilateral complete CLP deformity diagnosed as bilateral complete labiognatopalatoschizis. It was performed fabrication of nasolalveolar molding (NAM) in order to reduce the severity of the initial cleft deformity and to achieve better and more stable re-sults in CLP infants, in particularly advantageous to lengthen the deficient columella prior to the primary surgical re-pair of the lip and nose. Preliminary impression was done at the first appointment using custom tray and elastomeric material. At 2 weeks after birth, a conventional molding plate was fabricated on the maxillary cast. After the NAM was finished, try in was performed on the patient's mouth and adjustment were done to it edges. It is concluded that NAM allows an overall improvement in functional activity thus increasing infant’s weight prior to surgery, also correct the aesthetics of the nasolabial complex in bilateral cleft conditions while minimizing the extent of the sur-gery and the overall number of surgical procedures.